Phenolic compounds (hydroxycinnamic acids, flavan-3-ols, flavonols) profile in fruit of Italian peach varieties. (1st November 2016) - Ceccarelli, D.; Simeone, A. M.; Nota, P.; Piazza, M. G.; Fideghelli, C.; Caboni, E.
Abstract: Interest in phenolic compounds of fruit is growing due to their positive effects on reducing the risk of cardiovascular and carcinogen diseases. The role of the flesh colour, of the tissue (exocarp or mesocarp) and of the cultivar on the content of phenolic compounds (hydroxycinnamic acids, flavan-3-ols, flavonols) was evaluated in peach, Prunus persica (L.) Batsch, with a HPLC-DAD analysis, on 10 varieties deriving from the Italian breeding programmes, never previously characterized by this approach. The flavan-3-ols (catechin, epicatechin and procyanidin B1) were the most abundant class of phenolic compounds in peach cultivars analysed. Among hydroxycinnamic acids, neochlorogenic and chlorogenic acids were also identified and measured in the peach cultivars analysed. Quercetin-3-O-rutinoside was the only flavonol found in the exocarp of all the cultivars evaluated, but in the mesocarp of only some cultivars. Content of phenolic compounds was confirmed to be strongly dependent on the cultivar and, in general, the content was significantly higher in exocarp than in mesocarp. An overall significant difference in phenolic compounds as associated with flesh colour was not observed.